Physical, mechanical and morphological properties of sugar palm fiber reinforced polylactic acid composites - Shah Faisal Khan, Sherwani; Salit, Mohd Sapuan; Leman, Zulkiflle; Zainudin, Edi Syams; Abdan, Khalina (Springer, 2021)
This research was performed to evaluate the physical, mechanical and morphological properties of sugar palm fiber (SPF) reinforced polylactic acid (PLA) composites. PLA is a thermoplastic biodegradable polymer which is mostly used as a matrix material in the composite. Sugar palm fiber and PLA were mixed to form composite compounds using twin-screw extruder. These biocomposites of various sugar palm fiber loads (0, 10, 20, 30, and 40 wt. %) were prepared by using compression moulding. The effect of the loading of sugar palm fibers on the physical properties of composites (density, voids, and water absorption analysis), mechanical (tensile, flexural, and impact analysis) and morphology was studied. The determination of water absorption at different fiber loadings showed that the percentage of water absorption increased as the loading of fibers increased. The 30 % SPF loading composite displays optimum values for flexural and tensile strength which are 26.65 MPa and 13.70 MPa, respectively. Morphological studies by scanning electron microscopy revealed homogeneous fiber and matrix distribution also at 30 % loading of SPF with excellent adhesion, which plays an important role in enhancing the mechanical properties of composites. SEM analyzes show strong dispersion of SPF into PLA matrix.